2017
DOI: 10.1021/acs.bioconjchem.7b00194
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nanoparticle Contrast Agents for Cell Tracking with Computed Tomography

Abstract: Efforts to develop novel cell-based therapies originated with the first bone marrow transplant on a leukemia patient in 1956. Preclinical and clinical examples of cell-based treatment strategies have shown promising results across many disciplines in medicine, with recent advances in immune cell therapies for cancer producing remarkable response rates, even in patients with multiple treatment failures. However, cell-based therapies suffer from inconsistent outcomes, motivating the search for tools that allow m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
121
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(121 citation statements)
references
References 131 publications
0
121
0
Order By: Relevance
“… 12 Furthermore, inherent targeting of high-density lipoprotein particles 31 and cell labeling by GNPs were also successfully accomplished. 32 However, to the best of our knowledge there have been no reports on enzyme activity monitoring by the CT technique, most likely due to low sensitivity concerns. The goals of this work were to evaluate whether enzymatic activity can be detected by micro-CT, to assess the additional effect of protease targeting strategy compared to passive accumulation, and to select the optimal GNP size for visualization in vivo.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Furthermore, inherent targeting of high-density lipoprotein particles 31 and cell labeling by GNPs were also successfully accomplished. 32 However, to the best of our knowledge there have been no reports on enzyme activity monitoring by the CT technique, most likely due to low sensitivity concerns. The goals of this work were to evaluate whether enzymatic activity can be detected by micro-CT, to assess the additional effect of protease targeting strategy compared to passive accumulation, and to select the optimal GNP size for visualization in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, Galper et al compared the contrast enhancement of gold nanoparticles with iodinated compounds. They revealed that the contrast enhancement of gold nanoparticles at 120 kVp is 1.9 times higher than that of iodinated compounds (17). Kim et al (10) assessed the contrast enhancement of gold nanoparticles with that of iodine contrast agent in the range of 1 to 3 M. Their results showed that gold nanoparticles provide 1.9 times better contrast.…”
Section: Discussionmentioning
confidence: 99%
“…Cell tracking with X-ray CT is a rapidly developing field (J. Kim, Chhour, et al, 2017). Astolfo et al (2013) provided the first evidence for in vivo cell tracking using AuNP combined with CT. Malignant cells were labeled with AuNP and F I G U R E 7 (a) DECT iodine and gold maps for hindlimb sarcomas in the groups treated with 5 Gy RT in conjunction with no AuNP (control), PEGylated AuNP (non-targeted), or RGD-functionalized AuNP (targeted).…”
Section: Cell Tracking X-ray Agentsmentioning
confidence: 99%